2017
DOI: 10.3390/w9110834
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Downscaling of Suomi NPP–VIIRS Image for Lake Mapping

Abstract: Abstract:Capturing the dynamics of a lake-water area using remotely sensed images has always been an essential task. Most of the fine spatial resolution data are unsuitable for this purpose because of their low temporal resolution and limited scene coverage. A Visible Infrared Imaging Radiometer Suite on board the Suomi National Polar-orbiting Partnership (Suomi NPP-VIIRS) is a newly-available and appropriate sensor for monitoring large lakes due to its frequent revisits and wide swath (more than 3000 km). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Most of them are common subpixel mapping algorithms, which can be used for any kind of land cover. For surface water subpixel mapping in particular, there are some specific methods, such as those for lake water area mapping (Huang et al, ; Shah, ; Zhang et al, ), and those integrated with terrain information (Huang, Chen, & Wu, ; Ling et al, ). All of these methods took advantage of the special characteristics of surface water, such as spatial distribution or terrain dependency, and produced better results than normal subpixel mapping algorithms.…”
Section: Progresses and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them are common subpixel mapping algorithms, which can be used for any kind of land cover. For surface water subpixel mapping in particular, there are some specific methods, such as those for lake water area mapping (Huang et al, ; Shah, ; Zhang et al, ), and those integrated with terrain information (Huang, Chen, & Wu, ; Ling et al, ). All of these methods took advantage of the special characteristics of surface water, such as spatial distribution or terrain dependency, and produced better results than normal subpixel mapping algorithms.…”
Section: Progresses and Challengesmentioning
confidence: 99%
“…So far, most of the aforementioned studies were concentrated on a single procedure, either pixel unmixing or subpixel mapping, because the uncertainties inevitably introduced in each procedure would be multiplied and hard to be evaluated once these two were combined. In combining these two procedures to spatially downscale lake mapping, Huang et al () found that errors and uncertainties existed in both procedures, but mainly came from the spectral unmixing procedure.…”
Section: Progresses and Challengesmentioning
confidence: 99%
“…In addition to pre-calculated global surface water datasets, algorithms for detecting surface water from remote sensing data also have been created and applied at global, regional, and local scales. These include the thresholding of single bands and spectral indices [5][6][7][8][9][10][11][12]; simple decision trees relying on knowledge of the spectral properties of water compared to other land cover types [13][14][15]; spectral mixture analysis (SMA) [16][17][18], and supervised and unsupervised classification schemes (including machine learning algorithms) [19,20].The most common and simple method of identifying surface water using remotely sensed data is calculation of spectral indices. Many indices have been developed specifically to exploit the unique spectral signature of water compared to other land cover types [5][6][7][8][9][10]12,13].…”
mentioning
confidence: 99%
“…In addition to pre-calculated global surface water datasets, algorithms for detecting surface water from remote sensing data also have been created and applied at global, regional, and local scales. These include the thresholding of single bands and spectral indices [5][6][7][8][9][10][11][12]; simple decision trees relying on knowledge of the spectral properties of water compared to other land cover types [13][14][15]; spectral mixture analysis (SMA) [16][17][18], and supervised and unsupervised classification schemes (including machine learning algorithms) [19,20].…”
mentioning
confidence: 99%
“…Few studies exist on modelling shoreline using soft classification e.g. fuzzy c-means classification and the linear spectral mixture model (Dewi et al, 2016;Huang et al, 2017;Muslim et al, 2006;Taha and Elbeih, 2010). In our previous study, we used FCM classification to estimate the water memberships and then generate shoreline margin by using a choice of thresholds (Dewi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%